Trypanosomes and other blood parasites in slaughter cattle at Ibadan, Nigeria in 1984-1985 - Reynolds, L.; Opasina, B.A. (1987)
Over a 12-month period 313 (8.4 percent) out of 3727 slaughter cattle sampled at Ibadan abattoir were found to be infected with trypanosomiasis. Infection rates were higher in the dry than in the wet season ranging from 20.4 percent in November to 2.8 percent in May. Overall PCV levels were higher in dry season, suggesting that trypanosomiasis might not be the primary cause of anaemia. Trypanososomiasis is no longer a major problem in slaughter cattle at Ibadan, 98 percent of which come from northern areas.